Monitoring Soil Temperature and Humidity in an IoT-Based Green House to Improve Plant Management - Muthmainnah, Muthmainnah; Ninik Chamidah; Kusairi, Kusairi (Yayasan Insan Mulia Bima, 2024)
This study aims to develop and validate a soil temperature and humidity monitoring system using DHT 11 and YL 69 sensors connected to an ESP 8266 microcontroller. Calibration was performed by comparing sensor data with a reference instrument, followed by regression analysis to determine sensor accuracy. Validation involved calculating the standard deviation and accuracy of the sensor measurements. Temperature and soil humidity monitoring was conducted over five days in September, with average temperature measurements ranging from 22.4°C to 32.6°C and soil humidity ranging from 66.47% to 88.78%. The results showed that the temperature sensor had an average accuracy of 99.19%, while the humidity sensor had an average accuracy of 97.95%. The low standard deviation values for both sensors indicate good measurement consistency. These findings align with the literature emphasizing the importance of high-performance sensors for environmental monitoring in smart agriculture systems. The implementation of this system is expected to enhance the efficiency and effectiveness of agricultural management and support the sustainability of agricultural practices.